Local Sagittal Alignment of the Lumbar Spine and Range of Motion in 627 Asymptomatic Subjects: Age-Related Changes and Sex-Based Differences - Yasutsugu Yukawa; Taro Matsumoto; Heiko Kollor; Akihito Minamide; Hiroshi Hashizume; Hiroshi Yamada; Fumihiko Kato (Asian Spine Journal, 2019)
Study Design Prospective cohort imaging study. Purpose This study aimed to evaluate lumbar sagittal alignment and range of motion (ROM) using radiographs in a large asymptomatic cohort and identify sex-based differences and age-related changes in the subjects. Overview of Literature Several researchers have tried to establish normal alignment and kinematic behavior of the lumbar spine, using plain radiographs. Few studies have employed a large and sex-and age-balanced cohort. Methods Total 627 healthy volunteers (at least 50 males and 50 females in each age decade, from the 3rd to the 8th decade) underwent whole spine radiography in the standing position; lumbar spine radiography was performed for all subjects in the recumbent position. Lumbar lordosis (LL, T12–S1) and ROM during flexion and extension were measured using a computer digitizer. Results The mean LL was 36.8°±13.2° in the recumbent position and 49.8°±11.2° in the standing position. The LL was greater in the standing position than in the recumbent position; further, LL was higher in females as compared to that in males. Local lordosis at each disk level increased incrementally with distal progression through the lumbar spine in both the positions. Local lordosis at L4–S1 was 29.8°±8.0° in the recumbent position and 34.2°±8.3° in the standing position and occupied 85.1% and 70.8% of the total LL, respectively. However, local lordosis in the standing position decreased with age at L2–3, L3–4, and L4–5 levels. Total lumbar ROM (T12–S1) decreased with age. The ROM in females was higher than that in males. Conclusions We established the standard value and age-related changes in the lumbar alignment and ROM in each age decade in asymptomatic subjects. These data will be useful and provide the normal values for comparison in clinical practice to identify sex-based differences and age-related changes.